2009
DOI: 10.1210/jc.2009-0571
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling Protein-1 and Related Messenger Ribonucleic Acids in Human Epicardial and Other Adipose Tissues: Epicardial Fat Functioning as Brown Fat

Abstract: Because UCP-1 is expressed at high levels in epicardial fat as compared to other fat depots, the possibility should be considered that epicardial fat functions like brown fat to defend the myocardium and coronary vessels against hypothermia. This process could be blunted in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(138 citation statements)
references
References 16 publications
(15 reference statements)
5
124
0
3
Order By: Relevance
“…However, the presence and role of brown fat in humans is unclear. Very recently, expression of uncoupling protein-1 (UCP-1), a marker of brown fat, has been reported in human epicardial fat [21]. UCP-1 expression was significantly higher in human epicardial fat than in other fat depots, therefore suggesting that epicardial fat might function in the same way as brown fat to help to defend the myocardium and coronary artery against hypothermia (Figure 2) [21].…”
Section: Epicardial Adipose Tissue As Brown Fatmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the presence and role of brown fat in humans is unclear. Very recently, expression of uncoupling protein-1 (UCP-1), a marker of brown fat, has been reported in human epicardial fat [21]. UCP-1 expression was significantly higher in human epicardial fat than in other fat depots, therefore suggesting that epicardial fat might function in the same way as brown fat to help to defend the myocardium and coronary artery against hypothermia (Figure 2) [21].…”
Section: Epicardial Adipose Tissue As Brown Fatmentioning
confidence: 99%
“…Very recently, expression of uncoupling protein-1 (UCP-1), a marker of brown fat, has been reported in human epicardial fat [21]. UCP-1 expression was significantly higher in human epicardial fat than in other fat depots, therefore suggesting that epicardial fat might function in the same way as brown fat to help to defend the myocardium and coronary artery against hypothermia (Figure 2) [21]. UCP-1 expression was fivefold higher in epicardial fat than substernal fat and was largely undetectable in subcutaneous fat [21].…”
Section: Epicardial Adipose Tissue As Brown Fatmentioning
confidence: 99%
“…Recent studies have reported that human EAT expresses genes of the brown-like adipocytes, such as PGC1α, (UCP1), and PR-domain-missing 16 (PRDM16), suggesting that EAT may play a role in thermogenesis [13, 14]. However, it remains to be determined whether the brown fat-like gene expression in EAT is altered in CAD patients according to diabetes status.…”
Section: Introductionmentioning
confidence: 99%
“…subcutaneous vs. coronary) and that these profiles are significantly altered in the setting of disease. Examination of PVAT surrounding the major coronary arteries suggests that this adipose depot is phenotypically consistent with both white and brown adipose tissue 54, 55 . Data from the Weintraub laboratory indicate that adipocytes from human coronary PVAT exhibit a reduced state of adipogenic differentiation compared to adipocytes from other depots from the same subjects (e.g.…”
Section: Expression Profiles In Coronary Pvatmentioning
confidence: 97%